Case report: Kidney perivascular epithelioid cell tumor treated with anti-VEGFR tyrosine kinase inhibitor and MTOR inhibitor - Zhang, Ninggang; Ren, Yaqiong; Zan, Likun; Zhang, Xuting; Zhao, Jian; Wen, Lu; Wang, Yusheng (Frontiers in Oncology, 2022)
Perivascular epithelioid cell tumors (PEComas) are rare mesenchymal tumors arising from perivascular epithelial cells. There was no standard treatment for unresectable PEComa before 2021. For a low incidence and a rarely curable disease, development of new therapy is essential. A 45-year-old female was diagnosed with malignant renal PEComa (likely with TFE3 rearrangement) that underwent rapid progression after 10 months of surgery. The patient then received the tyrosine kinase inhibitor (TKI) Apatinib, and the tumor remained stable for 15 months before another progression. The patient then received the MTOR inhibitor everolimus that alleviated her symptoms but the tumor went into remission again after another 15 months. This result suggests that antagonizing the vascular endothelial growth factor receptor (VEGFR) pathway be a useful strategy for malignant PEComas, along with the MTOR pathway inhibition that had recently been approved for the rare tumor.